The Drosophila junctophilin gene is functionally equivalent to its four mammalian counterparts and is a modifier of a Huntingtin poly-Q expansion and the Notch pathway - Eduardo Calpena; Víctor López del Amo; Mouli Chakraborty; Beatriz Llamusí; Rubén Artero; Carmen Espinós; Máximo I. Galindo (The Company of Biologists, 2018)
Members of the Junctophilin (JPH) protein family have emerged as key actors in all excitable cells, with crucial implications for human pathophysiology. In mammals, this family consists of four members (JPH1-JPH4) that are differentially expressed throughout excitable cells. The analysis of knockout mice lacking JPH subtypes has demonstrated their essential contribution to physiological functions in skeletal and cardiac muscles and in neurons. Moreover, mutations in the human JPH2 gene are associated with hypertrophic and dilated cardiomyopathies; mutations in JPH3 are responsible for the neurodegenerative Huntington's disease-like-2 (HDL2), whereas JPH1 acts as a genetic modifier in Charcot-Marie-Tooth 2K peripheral neuropathy. Drosophila melanogaster has a single junctophilin (jp) gene, as is the case in all invertebrates, which might retain equivalent functions of the four homologous JPH genes present in mammalian genomes. Therefore, owing to the lack of putatively redundant genes, a jp Drosophila model could provide an excellent platform to model the Junctophilin-related diseases, to discover the ancestral functions of the JPH proteins and to reveal new pathways. By up- and downregulation of Jp in a tissue-specific manner in Drosophila, we show that altering its levels of expression produces a phenotypic spectrum characterized by muscular deficits, dilated cardiomyopathy and neuronal alterations. Importantly, our study has demonstrated that Jp modifies the neuronal degeneration in a Drosophila model of Huntington's disease, and it has allowed us to uncover an unsuspected functional relationship with the Notch pathway. Therefore, this Drosophila model has revealed new aspects of Junctophilin function that can be relevant for the disease mechanisms of their human counterparts.